An Investigation of the Influence of the 5E-LC Model on The Learning Outcome and Practical Performance of Vocational School Students - Saputro, Ida Nugroho; Hamid, Mustofa Abi; Nurtanto, Muhammad; Abdul Majid, Nuur Wachid; Rohmantoro, Didik (Journal of Technical Education and Training, 2025)
This study aimed to ascertain the impact of implementing the engagement, exploration, explanation, extension, and evaluation (5E) learning cycle model on learning outcomes and practical performance in vocational school subjects. This quantitative study employs a quasi-experimental design utilising a non-equivalent control group design. This study involved a control group and an experimental group. The study focused on vocational students in Serang City, and the sampling method employed was purposive sampling. The measures include multiple-choice tests for learning outcomes and practical performance questionnaires, utilising 4-point Likert scales. The data were analysed using the multivariate analysis of variance test and the independent sample test. The findings indicate a significant disparity between the average post-test scores of the experimental class and the control class. Furthermore, it shows a substantial disparity between the mean score of the experimental class in practice performance and the control class in practice performance. Therefore, it can be inferred that the 5E-LC model has an impact on both learning outcomes and practical performance in the field of electric lighting installation. In vocational secondary schools, teachers are required to possess the ability to apply the 5E-LC model in teaching subjects relevant to their field of study.